Bioterapia com Lucilia cuprina: atividade antimicrobiana e eficácia em feridas infectadas experimentalmente - Dillmann, Janaína Brand (2022)
Skin wounds are frequent in animals due to behavioral and management factors, and a subject of constant study due to their clinical, scientific, and economic interest. Although bacteria are part of the normal microbiota of the skin and wounds, the onset of an infection by their exacerbated proliferation and potential biofilm formation slows the healing process. In addition, inappropriate use of antibiotic therapy is a major cause of the spread of resistant microorganisms. Larval therapy emerges as an alternative for wound treatment, since necrophagous larvae such as the species Lucilia cuprina have present debridement potential, promote lesion cleansing by consuming local dead tissue and decrease the degree of infection, since bacteria are ingested and destroyed in the gut of the larvae. In addition to these benefits, pH change, stimulation of neovascularization, and tissue washing by induced local exudation accelerate the healing process. Thus, the objectives of this study were: (i) to evaluate the in vitro antimicrobial potential of L. cuprina larvae challenged by bacteria and (ii) to evaluate the efficacy and therapeutic safety of L. cuprina larvae on induced infected wounds in Wistar rats. Objective (i) was achieved by collecting whole body extracts from larvae incubated for 24 hours with a bacterial suspension of Staphylococcus aureus, Pseudomonas aeruginosa or methicillin-resistant S. aureus (MRSA). An antimicrobial analysis by Colony Forming Unit (CFU) assay was performed at two incubation times (0 and 6 hours) with pretreated and untreated (PBS) groups of larval extracts compared to a control group of bacterial growth. The results of experiment (i) showed significant activity against P. aeruginosa, a slight decrease in bacterial growth for S. aureus and MRSA. The results of objective (ii) were achieved through clinical, microbiological, histopathological analyses of the wounds and hematological and biochemical analyses of the animals. A significant shrinkage of the wound area (>95%) in the larvae-treated group was achieved at 9th day compared to 15th day in the antibiotic-treated group. There was complete elimination of MRSA colonies after the second treatment (6th day), compared to an increase in bacterial proliferation in the control group. On histopathology, a clean wound was observed in the larval treated group, as also adequate collagen formation and re-epithelialization on 15th day, and an increase in blood platelet levels in the hematological evaluation. It is then concluded that L. cuprina larvae are safe and effective in accelerating wound treatment and eliminating MRSA, and may represent an alternative for use in wound healing resistant to conventional treatments.